2010
DOI: 10.1007/s11259-010-9392-3
|View full text |Cite
|
Sign up to set email alerts
|

Cancer antigen 15/3: possible diagnostic use in veterinary clinical oncology. Preliminary study

Abstract: The cancer antigen 15/3 is a mucin that is associated with the cell membrane, encoded by the MUC1 gene, and recognized by the monoclonal-clone DF3 antibody. The latter antigen was discovered to be specific for both the identification of human mammary neoplasia and during patient follow-up evaluations. The aim of this study is to report and compare the results of the application of direct chemiluminescence in canine blood sera and the kit utilized in human medicine for the determination of Ca 15/3 to verify the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
2
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 10 publications
0
19
2
3
Order By: Relevance
“…A previous study that aimed to establish a method for CA15.3 testing in veterinary medicine, obtained a mean serum level of 2.77 ± 0.28 for the marker in dogs without neoplastic diseases . This result differs from the data obtained in our study, where in healthy female dogs, the mean serum level of CA15.3 was 1.37 ± 0.46.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…A previous study that aimed to establish a method for CA15.3 testing in veterinary medicine, obtained a mean serum level of 2.77 ± 0.28 for the marker in dogs without neoplastic diseases . This result differs from the data obtained in our study, where in healthy female dogs, the mean serum level of CA15.3 was 1.37 ± 0.46.…”
Section: Discussioncontrasting
confidence: 99%
“…These findings support the potential use of CA15.3 as a prognostic factor for mammary cancer in dogs. The latter antigen was found to be specific for the identification of mammary neoplasia and useful for monitoring of the disease . Furthermore, we observed that CEA could not be used as tumor marker because the serum concentration was not significantly different between healthy animals and animals with cancer.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Durante o trabalho, uma das dificuldades foi a escassez de valores de referência fato também evidenciado por Marchesi et al (2010) que realizaram a pesquisa com 57 amostras de soro e tecidos das fêmeas de cães com lesões mamárias neoplásicas e 24 amostras de soro de indivíduos clinicamente saudáveis para posterior comparação Marchesi et al (2010), com o método de quimiluminescência direta encontraram valores de 0.79±0.56 U/mL. Valores diferentes dos encontrados na presente pesquisa, podendo ser explicado pelo diferente método utilizado.…”
Section: Discussionunclassified
“…Em medicina veterinária Marchesi et al (2010), realizaram um trabalho de avaliação da concentração sérica e plasmática do CA 15-3 em cães, com o objetivo de determinar um valor de referência para a espécie. O estudo avaliou o marcador sérico em grupos de cadelas saudáveis e cadelas com diferentes lesões neoplásicas.…”
Section: Introductionunclassified